ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP KEMUNGKINAN PEMBERIAN OPINI AUDIT GOING CONCERN OLEH AUDITOR INDEPENDEN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2009-2011) - Ema Diandra Adjani; Surya Rahardja (Diponegoro Journal of Accounting, 2013)
The aim of this study is to examine the effect of the role of corporate governance to the possibilityof issuance of going concern audit opinion by an independent auditor. The independent variablesare used in this study is the proportion of independent directors, managerial ownership, andinstitutional ownership. This study is a replication of the study by Alexander et al., (2011) and used84 manufacturing companies which listed on the Stock Exchange in the period 2009-2011 as thesample. Samples were selected by purposive sampling method and finally obtained 38 companiesmanufacturing a going concern audit opinion and 46 manufacturing companies with non-goingconcern audit opinion. Data were analyzed using logistic regression analysis model. The resultsshow that the proportion of independent directors and institutional ownership has no effect on theissuance of going concern audit opinion by an independent auditor, while managerial ownershipaffect the administration going concern audit opinion by an independent auditor.